"Feeling Good" After Exercise During a Weight Loss Program: Subjective Well-Being in Support of a Hedonic Paradigm. Issue 1 (February 2023) - Berger, Bonnie G.; Darby, Lynn A.; Owen, David R.; Carels, Robert A.
A large portion of the U.S. population desires to lose weight, but only a small portion maintains a desirable body weight. We examined weight loss success and the psychological benefits of exercise among men and women who were obese and initially sedentary ( N = 33). These participants completed anthropometric assessments and psychological inventories before and after graded exercise tests (GXTs) at the beginning and end of their enrollment in a 6-month behavioral weight loss program (BWLP). Participants significantly decreased their body weight, body mass index (BMI), and % body fat; they also increased their aerobic capacity and exercise time. They reported long-term increases in their stage of change, self-efficacy, exercise enjoyment and processes of change. They also reported immediate changes toward more positive affect, as measured with pre-to post-GXTs on both the Profile of Mood States (POMS) and State Anxiety Subscale (A-State) at the beginning and again at end of the BWLP. Mood benefits were reported on the POMS subscales of Tension, Depression, Anger, Vigor, and Confusion. At the end of the BWLP, Fatigue and Confusion continued to improve after a 20-min post-GXT recovery period. Finally, reductions in Depression and Fatigue after the first GXT were correlated with program success, as indicated by decreases in BMI, percent body fat, and body weight. Initial scores on trait enjoyment were associated with decreased BMI and body weight. Psychological benefits of exercise may help individuals who are obese and sedentary change their behavior and exercise perceptions from something they "should do" to something they "want to do." Feeling good during weight loss efforts is an important pathway to change and should be an explicit component goal of BWLPs.